PENGARUH POSTINGAN INSTAGRAM #INDONESIAGELAP TERHADAP PERSEPSI MAHASISWA UNIVERSITAS PENDIDIKAN INDONESIA MENGENAI EFISIENSI DANA PENDIDIKAN - Lutfiah, Dita; Bestari, Prayoga; Supriatna, Aang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology has changed the way people obtain and disseminate information through social media. Instagram has become one of the platforms that greatly influences the formation of public opinion through visual content, information distribution algorithms, and hashtag features. Students, as digital natives, have a high intensity of social media usage, making them more exposed to issues developing in digital spaces. One phenomenon that has attracted public attention is the emergence of the hashtag #IndonesiaGelap, which often contains critical narratives regarding public policies, including the management of educational funding. This study aims to determine the influence of Instagram posts containing the hashtag #IndonesiaGelap on the perceptions of students at Universitas Pendidikan Indonesia regarding the efficiency of educational funding. This research employed a quantitative approach using a survey method involving 1,000 students selected through simple random sampling. Data were collected using closed-ended questionnaires with a Likert scale that had been tested for validity and reliability. The data were analyzed using simple linear regression to examine the relationship between exposure to Instagram posts and students’ perceptions. The results showed that posts containing the hashtag #IndonesiaGelap had a significant and negative influence on students’ perceptions of educational funding efficiency. This finding was supported by a t-value of -23.572 with a significance level of 0.000 (<0.05). The regression equation Y = 44.897 - 0.679X indicates that the higher the exposure to the content, the lower the students’ positive perception of educational funding efficiency. This study highlights the importance of digital literacy so that students can understand information critically and objectively.